2011
DOI: 10.1117/1.3621515
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of dehydration in porcine skin for assessing mechanism of optical clearing

Abstract: Abstract. Dehydration induced by optical clearing agents (OCAs) can improve tissue optical transmittance; however, current studies merely gave some qualitative descriptions. We develop a model to quantitatively evaluate water content with partial least-squares method based on the measurements of near-infrared reflectance spectroscopy and weight of porcine skin. Furthermore, a commercial spectrometer with an integrating sphere is used to measure the transmittance and reflectance of skin after treatment with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 33 publications
0
59
0
3
Order By: Relevance
“…Quantitative characterization of the OC mechanisms has been tried by measuring optical transmittance and re°ectance from porcine skin samples. 29 Similar studies have demonstrated that di®erent OCA di®usion enhancers (alcohols) provide signi¯-cant transmittance increase in porcine skin samples. 33 Sample thickness was also measured in these studies before and after the treatment, showing a small global variation.…”
Section: Introduction and Basic Conceptmentioning
confidence: 84%
See 1 more Smart Citation
“…Quantitative characterization of the OC mechanisms has been tried by measuring optical transmittance and re°ectance from porcine skin samples. 29 Similar studies have demonstrated that di®erent OCA di®usion enhancers (alcohols) provide signi¯-cant transmittance increase in porcine skin samples. 33 Sample thickness was also measured in these studies before and after the treatment, showing a small global variation.…”
Section: Introduction and Basic Conceptmentioning
confidence: 84%
“…The dehydration mechanism in particular, has been widely investigated using di®erent techniques that involves mechanical and temperature variation methods to remove water from tissue area under study. 11,[28][29][30][31] These studies reported that the water loss provides a greater tissue transparency through the combination of the smaller sample thickness and the better ordering of scatterers.…”
Section: Introduction and Basic Conceptmentioning
confidence: 99%
“…3 demonstrates that decreasing the tissue temperature resulted in decreasing the µ's and, therefore, increasing the PI and TI which means enhancement of photon density in the dermis. As described in previous studies, such results may be caused by the modification of collagen fiber structure, degradation of cellular components, and change of the refractive index of intercellular fluid [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 96%
“…Skin dehydration and collagen dissociation may cause the reduction of light scattering by minimizing refractive index mismatching [15][16][17]. Recently, Yu et al [19] reported that the dehydration induced by an optical clearing agent is a prominent mechanism for improving tissue optical transmittance. Direct injection of glycerol may have a clinical advantage of an immediate OTC effect in local treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation